Preliminary report on human remains from Qasr Shemamok (Erbil, Federal region of Iraqi Kurdystan). Season 2012 - Jacek Tomczyk (Studia Ecologiae et Bioethicae)
Qasr Shemamok, a large tell situated about 30 km southwest of Erbil, close to the village of Tarjan, is a well-known site of Iraqi Kurdistan. It has been identified as the remains of the ancient city of Kakzu (or Kilizu) since the 19th century. In 2012, a French archaeological Mission, guided by O. Rouault with a European team, and funded by the French Ministry of Foreign Affairs, came to work in Erbil, answering an invitation from the Kurdish authorities, and from the Erbil Salaheddin University, thanks to the strong support of the local French Consulate. The text presents the first results of the anthropological work at Qasr Shemamok, conducted in the 2012 season.